PENGARUH KEPUASAN KERJA DAN KETERIKATAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT XYZ DI ROKAN HULU RIAU - Ronaldo Sinaga, Harry; Absah, Yeni; Rahim Matondang, A (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research aims to thoroughly analyze the influence of job satisfaction and employee engagement on employee performance at XYZ Palm Oil Plantation Company located in Rokan Hulu, Riau. In an increasingly competitive plantation industry era, human resource factors such as job satisfaction and employee engagement play a crucial role in determining the company's success. This study employs a quantitative approach with a survey method, involving a total of 100 respondents selected based on specific criteria to represent the entire workforce of the company. Data were collected through questionnaires designed with relevant measurement indicators, such as satisfaction levels regarding the work environment, compensation, relationships with supervisors and colleagues, as well as emotional attachment and commitment to the company. Data analysis was conducted using multiple linear regression methods to examine the influence of independent variables on the dependent variable. The results indicate that both job satisfaction and employee engagement have positive and significant effects on employee performance. This suggests that higher levels of satisfaction and engagement among employees will positively impact their productivity and work quality. These findings highlight that management should focus more on improving aspects that contribute to employee satisfaction and engagement as key strategies to enhance performance and ensure sustainable company growth. Additionally, the study emphasizes the importance of human resource management oriented toward employee well-being to create a conducive work environment, increase loyalty, and boost motivation. With increased satisfaction and engagement, it is expected that the company can achieve optimal production targets, maintain operational sustainability, and strengthen its competitive position in the regional and national palm oil industry.